The night travellers - Spencer, Elizabeth, 1921-2019 (Banner Books, 2012)
Elizabeth Spencer is "a master storyteller" (San Francisco Chronicle), her work called "dazzling" by Walker Percy. Whether she's writing short stories or novels, Spencer is acclaimed for holding her worlds up to light and turning them to see what they reflect. The Night Travellers, set in North Carolina and Montreal during the Vietnam War years, is her most revealing work yet. Mary Kerr Harbison is a promising teenaged dancer when she meets Jefferson Blaise, an intellectual radical-in-the-making. He becomes a part of her life and over the objections of Mary's wealthy, abusiv.